The impact of parental involvement on academic student achievement - Eldeeb, Ayman Mokhtar Zaher (2012)
As long as there is an educational system, there is always a need to improve that system along with its outcomes. Student’s achievement, among other factors, is one major component as well as a measure of how effective the system is. The purpose of this study is to determine whether parental involvement in children's education has a positive effect on student’s achievement. While the quantitative approach was very cooperative in the study in hand, for example the researcher was able to gather general information of the study sample, and the qualitative method facilitated in understands the meanings the interviewees carry to it. Both methodologies were used because even though they are different in many ways, they supplement each other. The study found that there is a positive correlation effect between academic achievement and parental involvement. On the other hand the participants’ responses showed that the school current program for “school-parents interaction” has many defects which need to be reformed to bring more attention to parents’ involvement topic and to be able to attract them for more involvement. The study is important because it applied current research to statistical tests on local students. The results obviously display the way by which schools must travel to increase student’s achievement throughout effective parental involvement.